Extracellular adenosine levels are associated with the progression and exacerbation of pulmonary fibrosis. Issue 2 (2nd November 2015) - Luo, Fayong; Le, Ngoc‐Bao; Mills, Tingting; Chen, Ning‐Yuan; Karmouty‐Quintana, Harry; Molina, Jose G.; Davies, Jonathan; Philip, Kemly; Volcik, Kelly A.; Liu, Hong; Xia, Yang; Eltzschig, Holger K.; et al.
Abstract : Idiopathic pulmonary fibrosis is a devastating lung disease with limited treatment options. The signaling molecule adenosine is produced in response to injury and serves a protective role in early stages of injury and is detrimental during chronic stages of disease such as seen in lung conditions such as pulmonary fibrosis. Understanding the association of extracellular adenosine levels and the progression of pulmonary fibrosis is critical for designing adenosine based approaches to treat pulmonary fibrosis. The goal of this study was to use various models of experimental lung fibrosis to understand when adenosine levels are elevated during pulmonary fibrosis and whether these elevations were associated with disease progression and severity. To accomplish this, extracellular adenosine levels, defined as adenosine levels found in bronchio‐alveolar lavage fluid, were determined in mouse models of resolvable and progressive pulmonary fibrosis. We found that relative bronchioalveolar lavage fluid adenosine levels are progressively elevated in association with pulmonary fibrosis and that adenosine levels diminish in association with the resolution of lung fibrosis. In addition, treatment of these models with dipyridamole, an inhibitor of nucleoside transporters that potentiates extracellular adenosine levels, demonstrated that the resolution of lung fibrosis is blocked by the failure of adenosine levels to subside. Furthermore, exacerbating adenosine levels led to worse fibrosis in a progressive fibrosis model. Increased adenosine levels were associated with elevation of IL‐6 and IL‐17, which are important inflammatory cytokines in pulmonary fibrosis. These results demonstrate that extracellular adenosine levels are closely associated with the progression of experimental pulmonary fibrosis and that this signaling pathway may mediate fibrosis by regulating IL‐6 and IL‐17 production.—Luo, F., Le, N.‐B., Mills, T., Chen, N.‐Y., Karmouty‐Quintana, H., Molina, J. G., Davies, J., Philip, K., Volcik, K. A., Liu, H., Xia, Y., Eltzschig, H. K., Blackburn, M. R. Extracellular adenosine levels are associated with the progression and exacerbation of pulmonary fibrosis. FASEB J. 30, 874–883 (2016). www.fasebj.org